Effect of Ginger (Zingiber officinale) extracts on mechanical and antimicrobial properties of Ganyong starch edible films as primary packaging of crabstick - Silvia, Deli; Zulkarnain, Zulkarnain; Fadhilah, Rizki Ivan; Kamilah, Hanisah; Abdul Karim Shah, Nor Nadiah (Walailak University, 2024)
Research has been conducted on the effect of ginger (Zingiber officinale) extract addition in the combination of an edible film made from Ganyong starch, sorbitol and chitosan. This study aims to analyze whether this formulation can be used as a substitute packaging for crabsticks that have been using conventional plastic packaging. By using a variation of ginger extract concentrations of 0, 3%, 6% and 9% into 3 % Ganyong starch, 4 % sorbitol and 0.3 % chitosan (w/v). Mechanical characteristics were carried out in the form of tensile strength, elongation, young modulus, swelling, moisture content, thickness, and solubility test. Antimicrobial ability and DSC (Differential scanning calorimetry) for the thermal properties of the casted film were also conducted. Data was analyzed using One-way Anova SPSS version 29 with Turkey’s test. The addition of ginger extract to edible films based on Ganyong starch, sorbitol and chitosan can be used as primary packaging for crabsticks. The best formulation was found in the 6 % ginger extract variation with the results of swelling (95 %), moisture content (13 %), elongation (76 %), and antimicrobial properties of Escherichia coli (7.5 mm) and Bacillus cereus (6.9 mm). In addition, the melting temperature (Tm) of 6 % ginger extract concentration was also higher (134 °C), yet was not significantly different from the other variations. Therefore, this formulation has the potential as an alternative primary crabstick packaging.